2002
DOI: 10.1007/s00115-002-1334-z
|View full text |Cite
|
Sign up to set email alerts
|

Chronifizierung und psychosoziale Behinderung durch depressive Erkrankungen bei Patienten in der Allgemeinarztpraxis im Einjahresverlauf Ergebnisse aus einer Studie der Weltgesundheitsorganisation

Abstract: As part of an international WHO study on psychological disorders in primary health care, patients were examined for mental disorders and especially depression and social disability in the course of 1 year. Depression is common in primary care (8.6%) and frequently associated with recurring or chronic courses (33.3%). Depression at baseline leads to a 100% increase of lost working days (3.2 per month) 1 year later as compared to patients without depression (1.7). The diagnosis of depression at baseline poses a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0
7

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 15 publications
1
4
0
7
Order By: Relevance
“…This is in concordance with the literature (Kühn et al, 2002;Buist-Bouwman et al, 2006) which has shown that mental disorders are associated with high rates of disability.…”
Section: Discussionsupporting
confidence: 93%
“…This is in concordance with the literature (Kühn et al, 2002;Buist-Bouwman et al, 2006) which has shown that mental disorders are associated with high rates of disability.…”
Section: Discussionsupporting
confidence: 93%
“…Hierbei muss jedoch berücksichtigt werden, dass in diese Prävalenzrate sowohl Menschen eingehen,die neben Ihrer körperlichen Erkrankung an einer komorbiden Depression leiden,als auch solche,die mit psychischen Symptomen bzw.körperlichen Symptomen ohne organische Ursache in die Arztpraxis kommen und bei denen eine Depression ohne körperliche Erkrankung besteht. Das Vorliegen einer körperlichen Erkrankung stellt aber auch in diesen Stichproben ein Risiko für Depression dar und bildet einen ungünstigen Faktor für die weitere Prognose der depressiven Störung.Eine Nachuntersuchung der deutschen Teilstichprobe der WHO-Hausarzt-Studie ergab, dass nach 1 Jahr bei 1/3 der Fälle ein rezidivierender oder chronischer Verlauf vorlag, der auch zu einem hohen Grad von sozialer Behinderung führte [59].…”
Section: Häufigkeit Und Verlauf Depressiver Störungen Bei Körperlich unclassified
“…Subsyndromale bzw. minore Formen der Depression sind dabei mit einem erhöhten Risiko für die Entste− hung einer Major Depression verbunden [16]. Dies gilt ersten Er− gebnissen zufolge auch für die depressive Persönlichkeitsstö− rung [17].…”
Section: Introductionunclassified